Desorption spectrometry II: coupled desorption of Li marker and degradation of polypyrrole. Issue 3 (3rd March 2020) - Hnatowicz, V.; Vacik, J.; Cervena, J.
Abstract : In this work, different aqueous Lithium salt markers were introduced into polypyrrole, thereafter the system was dried, and finally water was again allowed to enter with the aim to desorb the incorporated Li marker. The Li desorption is closely followed by the Neutron Depth Profiling technique. It turns out that the desorption spectra strongly depend on the solubility of the applied markers, and furthermore, the polymer-water interaction influences the outcome. Finally, there are hints that the Li markers incorporated within the polymeric free volume may undergo chemical bonds with the polymer. Especially the desorption of incorporated LiF from the polymer leads to very peculiar Li depth distributions which closely resemble the well-known Case II diffusion profiles, with steep profile concentration changes emerging at the front of the water penetration from the outside.